1997
DOI: 10.1002/j.1875-9114.1997.tb03746.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceftibuten: An Overview

Robert C. Owens,
Charles H. Nightingale,
David P. Nicolau

Abstract: Ceftibuten is an orally active third‐generation cephalosporin that exhibits good microbiologic activity against many gram‐negative and select gram‐positive organisms. It is stable against plasmid‐mediated β‐lactamases, including extended‐spectrum β‐lactamases. Ceftibuten has been shown to be effective in the treatment of upper and lower respiratory tract infections and, although not approved indications, complicated and uncomplicated urinary tract infections in both adults and children. It is readily absorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Ceftibuten is a cephalosporin antibiotic approved in the USA ( 4 ) for acute exacerbations of chronic bronchitis, acute bacterial otitis media, and pharyngitis/tonsillitis at a dose of 400 mg once-daily for up to 10 days ( 5 7 ). The safety profile of ceftibuten is similar to other cephalosporin antibiotics with nausea (4%), headache (3%), diarrhea (3%), dyspepsia (2%) and dizziness, abdominal pain, and vomiting (all 1%) being the most common adverse reactions in the US Food and Drug Administration label ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftibuten is a cephalosporin antibiotic approved in the USA ( 4 ) for acute exacerbations of chronic bronchitis, acute bacterial otitis media, and pharyngitis/tonsillitis at a dose of 400 mg once-daily for up to 10 days ( 5 7 ). The safety profile of ceftibuten is similar to other cephalosporin antibiotics with nausea (4%), headache (3%), diarrhea (3%), dyspepsia (2%) and dizziness, abdominal pain, and vomiting (all 1%) being the most common adverse reactions in the US Food and Drug Administration label ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics (PK) of ceftibuten has been characterized in single- and multiple-dose studies in the range of 25–800 mg ( 9 16 ). Previous studies have shown that ceftibuten is very well absorbed after oral administration of doses up to 400 mg, with a bioavailability between 75% and 90% ( 6 , 7 , 13 , 16 ). Maximum plasma concentrations are reached within 2–3 h ( 9 , 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%